The Association of Work Environments and Nurse-Nurse Collaboration: A Multicenter Cross-Sectional Study - Ghasemi, Roya; Ghafourifard, Mansour; Hassankhani, Hadi; Dehghannezhad, Javad (Nurse Media Journal of Nursing, 2021)
Background: Along with the recent healthcare reform, intraprofessional collaboration in nursing is considered an essential factor for managing the challenges related to diverse roles and tasks of nurses in providing high quality care. There is lack of knowledge on how the nursing work environment could influence nurse-nurse collaboration.   Purpose: The study aimed to assess the relationship between nursing work environment and nurses’ intraprofessional collaboration.Methods: A total of 300 nurses working in four teaching hospitals participated in this multicenter cross-sectional study. Data were collected using the Nurse-Nurse Collaboration Scale (NNCS) and the Practice Environment Scale of the Nursing Work Index (PES–NWI). The Pearson correlation test was used to analyze the data.Results: The results showed that the mean score of the PES–NWI was 2.65±0.32 out of 4. The highest and lowest scores belonged to the subscales of the nursing foundations for quality of care (2.86±0.31) and staffing and resource adequacy (2.24±0.49), respectively. The mean total score of nurse-nurse collaboration was 2.94±0.21 out of a score of 4. The results showed a significant positive relationship between nursing work environment and nurses’ intraprofessional collaboration (r=0.49, p<0.05).Conclusion: The nursing practice environment has a positive and significant relationship with nurse-nurse collaboration. Therefore, improving nurses’ practice environment and providing healthy workplaces could improve the intraprofessional nurse’s collaboration. Moreover, nurse managers should improve nurses’ skills in some areas of collaboration such as conflict management.